2018
DOI: 10.3389/fimmu.2018.00171
|View full text |Cite
|
Sign up to set email alerts
|

Integrase Defective Lentiviral Vector as a Vaccine Platform for Delivering Influenza Antigens

Abstract: Viral vectors represent an attractive technology for vaccine delivery. We exploited the integrase defective lentiviral vector (IDLV) as a platform for delivering relevant antigens within the context of the ADITEC collaborative research program. In particular, Influenza virus hemagglutinin (HA) and nucleoprotein (NP) were delivered by IDLVs while H1N1 A/California/7/2009 subunit vaccine (HAp) with or without adjuvant was used to compare the immune response in a murine model of immunization. In order to maximize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Integrase-defective lentiviral vectors have been designed as a vaccine platform to deliver vaccination against influenza and malaria antigens. 324 , 325 Such lentiviral vectors are being continuously developed and optimized, and could enjoy a broader application in future gene therapies. In addition, the development of safer vectors via photo-switchable non-canonical amino acids to regulate transgene expression in a spatial and temporal manner, 326 also represent the next generation of lentiviral vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Integrase-defective lentiviral vectors have been designed as a vaccine platform to deliver vaccination against influenza and malaria antigens. 324 , 325 Such lentiviral vectors are being continuously developed and optimized, and could enjoy a broader application in future gene therapies. In addition, the development of safer vectors via photo-switchable non-canonical amino acids to regulate transgene expression in a spatial and temporal manner, 326 also represent the next generation of lentiviral vectors.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown, in both mice and macaque studies, that integrase defective lentiviral vectors (IDLV) provide prolonged antigen expression and can induce potent and durable antigenspecific immune responses [9][10][11][12][13] . We demonstrated that immunization with an SIV-based IDLV expressing an HIV-1 Env induces continued antibody affinity maturation up to three months postprime, which is further improved upon additional IDLV-Env immunizations 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we found that vaccination with IDLV expressing the conserved IAV nucleoprotein (IDLV-NP) can induce broad protective immunity against challenge with several IAV subtypes [ 35 , 40 ]. However, IDLV-NP requires two immunizations to be effective, thereby making it not suitable for inducing rapid protection.…”
Section: Resultsmentioning
confidence: 99%
“…administration of IDLV expressing IAV NP (IDLV-NP) can induce broad protective immunity against challenge with several IAV subtypes. However, this approach requires two administrations over the course of a month to be effective [ 35 , 40 ], thereby making it not suitable for inducing rapid protection. In the experiments described above, IDLV-VN04-2 achieved rapid protection against IAV in mice, although the protection did not persist at 30 days post-administration.…”
Section: Discussionmentioning
confidence: 99%